Intraspecific carbon and nitrogen isotopic variability in foxtail millet (Setaria italica). (7th June 2016) - Lightfoot, Emma; Przelomska, Natalia; Craven, Martha; O′Connell, Tamsin C.; He, Lu; Hunt, Harriet V.; Jones, Martin K.
Abstract : Rationale: Isotopic palaeodietary studies generally focus on bone collagen from human and/or animal remains. While plant remains are rarely analysed, it is known that plant isotope values can vary as a result of numerous factors, including soil conditions, the environment and type of plant. The millets were important food crops in prehistoric Eurasia, yet little is known about the isotopic differences within millet species. Methods: Here we compare the stable isotope ratios within and between Setaria italica plants grown in a controlled environment chamber. Using homogenised samples, we compare carbon isotope ratios of leaves and grains, and nitrogen isotope ratios of grains, from 29 accessions of Setaria italica . Results: We find significant isotopic variability within single leaves and panicles, and between leaves and panicles within the same plant, which must be considered when undertaking plant isotope studies. We find that the leaves and grains from the different accessions have a ca 2‰ range in δ 13 C values, while the nitrogen isotope values in the grains have a ca 6‰ range. We also find an average offset of 0.9‰ between leaves and grains in their δ 13 C values. Conclusions: The variation found is large enough to have archaeological implications and within‐ and between‐plant isotope variability should be considered in isotope studies. The range in δ 15 N values is particularly significant as it is larger than the typical values quoted for a trophic level enrichment, and as such may lead to erroneous interpretations of the amount of animal protein in human or animal diets. It is therefore necessary to account for the variability in plant stable isotope values during palaeodietary reconstructions. Copyright © 2016 John Wiley & Sons, Ltd.